EFFECT OF PIPERINE ON GOAT EPIDIDYMAL SPERMATOZOA: AN IN VITRO STUDY - Janarthanan, Rajesh; Chinta, GopiChand; Jesthadi, Dineshbabu; Shanmuganathan, Bavatharini; Periyasamy, Latha (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â  Â Objective: Fertility control is a global issue in the perspective of health and economy worldwide. Many of the investigations were carried out to prove the anti-fertility effect of the traditional natural products in males. Until today, there is no such reversible contraceptive is available for males. Piperine is a versatile bioactive compound being used from the centuries to treat domestic animal illness as well as in humans. This study was aimed to evaluate the effect of piperine on goat epididymal spermatozoa in vitro. Methods: Goat sperms were incubated with piperine at the doses of 40 Î¼mol/L, 60 Î¼mol/L, 80 Î¼mol/L, 100 Î¼mol/L for 3 hrs. After 3 hrs parameters such as motility, viability, superoxide dismutase (SOD), Catalase (CAT) activities, and lipid peroxidation (LPO) level was monitored. Hypo-smotic swelling test and acridine orange test were performed. Results: Significant decrease in motility, viability, SOD, CAT activities of goat epididymal sperm was observed after 3 hrs of incubation with piperine. Significant increase in LPO levels was found after 3 hrs of incubation with piperine at above mentioned doses. Piperine produced significant disruption in the functional integrity and also damaged the DNA of goat epididymal sperm. Conclusion: From the above results, we can conclude that increase in the oxidative damage and functional disruption of sperm by piperine might be one of the reasons for its anti-fertility activity. Keywords: Piperine, Anti-fertility agent, Superoxide dismutase, Catalase, Lipid peroxidation.